2013
DOI: 10.1017/s0954579412000892
|View full text |Cite
|
Sign up to set email alerts
|

Childhood temperament: Passive gene–environment correlation, gene–environment interaction, and the hidden importance of the family environment

Abstract: Biological parents pass on genotypes to their children, as well as provide home environments that correlate with their genotypes; thus, the association between the home environment and children's temperament can be genetically (i.e. passive gene-environment correlation) or environmentally mediated. Furthermore, family environments may suppress or facilitate the heritability of children's temperament (i.e. gene-environment interaction). The sample comprised 807 twin pairs (M age = 7.93 years) from the longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 103 publications
(143 reference statements)
5
58
1
Order By: Relevance
“…However, according to the T X E perspective, children’s outcomes can be best explained by the interaction between children’s temperamental characteristics (e.g., EC) and their environment (e.g., classroom chaos; Rothbart & Bates, 2006). In support of the T X E hypothesis, a large body of literature demonstrates that chaos in the home environment moderates the association between child characteristics and behavioral and socioemotional adjustment outcomes, such that children with more difficult temperamental characteristics have more optimal outcomes when chaos is low than when chaos is high (Chen, Deater-Deckard, & Bell, 2014; Lemery-Chalfant, Kao, Swann, & Goldsmith, 2013; Wang, Deater-Deckard, Petrill, & Thompson, 2012). Although home chaos is different than classroom chaos, this literature provides a foundation for conceptualizing the role of classroom chaos in school adjustment.…”
Section: Introductionmentioning
confidence: 95%
“…However, according to the T X E perspective, children’s outcomes can be best explained by the interaction between children’s temperamental characteristics (e.g., EC) and their environment (e.g., classroom chaos; Rothbart & Bates, 2006). In support of the T X E hypothesis, a large body of literature demonstrates that chaos in the home environment moderates the association between child characteristics and behavioral and socioemotional adjustment outcomes, such that children with more difficult temperamental characteristics have more optimal outcomes when chaos is low than when chaos is high (Chen, Deater-Deckard, & Bell, 2014; Lemery-Chalfant, Kao, Swann, & Goldsmith, 2013; Wang, Deater-Deckard, Petrill, & Thompson, 2012). Although home chaos is different than classroom chaos, this literature provides a foundation for conceptualizing the role of classroom chaos in school adjustment.…”
Section: Introductionmentioning
confidence: 95%
“…For example, Lemery-Chalfant and colleagues [3] found that heritability of negative affectivity increased under crowded or unsafe home conditions, exemplifying the complex and influential interaction between genetic and environmental factors on temperament.…”
Section: Discussionmentioning
confidence: 99%
“…This third model is an integrated form of the trait and the developmental pathways models, the outlines of which are at least implicit in the theorizing of Bronfenbrenner and others (Bronfenbrenner & Ceci, 1994;Wachs, 2009;Lemery-Chalfant, Kao, Swann, & Goldsmith, 2013) and were explicitly endorsed by Figueredo and colleagues (2015), in which the influences of both the permanent and stable individual difference trait and the outcomes of psychosocial interactions at each stage of development upon the outcomes of interactions at the next stage are also explicitly included. Once again, as the particular individual difference trait involved has been shown to be highly heritable (Figueredo et al, 2004;Figueredo & Rushton, 2009), these influences could be characterized as falling mostly within the conventional behavioral-genetic category of gene-environment interactions (encompassing the passive, evocative, and active versions of the same; see DiLalla & Gottesman, 1991;Plomin, DeFries, & Loehlin, 1977), in that both the latent trait and the outcomes of each immediately prior developmental stage are hypothesized to influence the outcomes at each successive stage in systematically dissimilar ways for different individuals, depending on both one's level of the trait and on the specific social interactions encountered at each successive in of environment.…”
Section: Discussionmentioning
confidence: 99%